Enhancing Pedagogical Competence and Administrative Management in Qur'anic Education Centers: Implementation of the Ummī Method in Planjan Village - Hud, Ibnu muhammad yusuf; Aprianto; Maryono (ASSUNNAH PRESS, 2025)
This research examines the implementation of the Ummī method and structured administrative documentation to enhance pedagogical competence and administrative management in Qur'anic Education Centers (TPA) in Planjan Village. The study involved eight TPA teachers who participated in training focused on two main components: the Ummī method for Qur'anic teaching and structured administrative documentation. The Ummī method emphasizes a reading-listening technique where students listen to correct Qur'anic recitation before imitating it, while the structured administrative documentation included student progress records and daily prayer and remembrance books. Questionnaire results revealed significant improvements in teaching abilities and administrative management, with 7 out of 8 participants reporting positive changes in their pedagogical approach and confidence in classroom management. The implementation of more structured administrative documentation enabled teachers to monitor student progress more effectively and provide constructive feedback. Despite some challenges, including participants needing more time to fully master the new techniques, the training successfully enhanced religious education quality in Planjan Village TPAs, providing a potential model for other Qur'anic Education Centers.